Pengaruh Produksi Kelapa Sawit Dan Tenaga Kerja Pada Pendapatan Usaha Kelapa Sawit Di Desa Bangun Purba - Glen Maigo Kalista Sembiring; Marizha Nurcahyani; Sri Ariani Safitri (Universitas Medan Area, 2026)
Oil palm is a tropical plant that produces the main vegetable oil that is widely cultivated to meet the needs of the food, cosmetics, and energy industries. The purpose of this study was to see the effect of oil palm production and labor on the income of oil palm businesses in Bangun Purba Village using the multiple linear regression method and using 37 samples. The results of this study indicate that oil palm production has a very significant effect on farmers' income, with a t-value of 19.456 and a significance of 0.001, where the higher the production, the greater the income obtained. In addition, labor also contributes to increasing farmers' income, with a t-value of 3.040 and a significance of 0.001, although its effect is smaller than oil palm production. Overall, the results of the F test show that oil palm production and labor simultaneously have a significant effect on farmers' income, with a calculated F value of 25.123 and a significance of 0.001, so that optimizing these two factors is key to improving their welfare. This study concludes that palm oil production and labor have a significant effect on farmers' income, increasing both of which can improve their welfare.